2022
DOI: 10.3390/cells11060998
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of Leguminous and Non-Leguminous Desert Plant Species Does Not Facilitate Phosphorus Mineralization and Plant Nutrition

Abstract: More efficient use of soil resources, such as nitrogen (N) and phosphorus (P), can improve plant community resistance and resilience against drought in arid and semi-arid lands. Intercropping of legume and non-legumes can be an effective practice for enhancing P mineralization uptake, and plant nutrient status. However, it remains unclear how intercropping systems using desert plant species impact soil-plant P fractions and how they affect N and water uptake capacity. Alhagi sparsifolia (a legume) and Karelini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Soil serves as a habitat for microorganisms, with intricate relationships flourishing [37]. Previous studies have proposed that increasing the diversity of soil bacterial communities enhances the association of soil microbial species, thus improving soil ecological stability [38][39][40]. Consistent with these findings, we observed a significant increase in bacterial community diversity and richness under intercropping (Figure 2A).…”
Section: Intercropping Significantly Influences the Microbial Communi...supporting
confidence: 89%
“…Soil serves as a habitat for microorganisms, with intricate relationships flourishing [37]. Previous studies have proposed that increasing the diversity of soil bacterial communities enhances the association of soil microbial species, thus improving soil ecological stability [38][39][40]. Consistent with these findings, we observed a significant increase in bacterial community diversity and richness under intercropping (Figure 2A).…”
Section: Intercropping Significantly Influences the Microbial Communi...supporting
confidence: 89%
“…This suggests that despite the yield advantages of intercropping, soil nutrients are gradually depleted with increasing years of cultivation without nutrient input. Many studies have showed that the efficient use of resources determines whether there was an advantage in grain yield, and the balance between competition and interaction in the intercropping system was the key to the effective utilization of resources (Tsialtas et al 2018;Han et al 2020;Tariq et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Research in hyper‐arid desert ecosystems has found that the concentrations of soil labile P and foliar total P are much lower in desert plants than in other species (Gao et al, 2022a, b). To adapt to P‐poor soils, desert species have adopted flexible strategies of allocation among distinct foliar P fractions; for example, allocating more foliar P to structural or genetic material (Gao et al, 2022a; Tariq et al, 2022b). Changing the morphological traits of roots, increasing root APase activity, and releasing more carboxylates are strategies for roots to adapt to low P in soils (Gao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%